IMPACT ASSESSMENT IN REHABILITATION OF TORTURE SURVIVORS. Part II: An exploratory study of outcome of torture rehabilitation at specialised centres from the clients' and health professionals' perspective - Amris, Stine; G. Arenas, Julio (Psyke & Logos, 2004)
Summary of this article can be found at page 401-402